2006
DOI: 10.1007/s10601-006-7094-9
|View full text |Cite
|
Sign up to set email alerts
|

Constraint Models for the Covering Test Problem

Abstract: Covering arrays can be applied to the testing of software, hardware and advanced materials, and to the effects of hormone interaction on gene expression. In this paper we develop constraint programming models of the problem of finding an optimal covering array. Our models exploit global constraints, multiple viewpoints and symmetry-breaking constraints. We show that compound variables, representing tuples of variables in our original model, allow the constraints of this problem to be represented more easily an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(69 citation statements)
references
References 22 publications
1
68
0
Order By: Relevance
“…These tools accept a test model and constraints as input data and generate the set of test cases. In addition, in [9], we showed how constraints can be handled when constraint programming is used to construct test cases [10], [11]. Table 3 represents a set of test cases for the cross-browser testing constructed with considering constraints.…”
Section: Pair-wise Testing and Constraintsmentioning
confidence: 99%
“…These tools accept a test model and constraints as input data and generate the set of test cases. In addition, in [9], we showed how constraints can be handled when constraint programming is used to construct test cases [10], [11]. Table 3 represents a set of test cases for the cross-browser testing constructed with considering constraints.…”
Section: Pair-wise Testing and Constraintsmentioning
confidence: 99%
“…The SAT solver is a program for checking logical constraints [19], [22], [23]. The solver checks validity and consistency.…”
Section: Evaluate Logical Formulasmentioning
confidence: 99%
“…Prestwich, E. Selensky, B.M. Smith [9] have developed models for constraint programming for finding an optimal covering array. It is shown that the compound variables that represent tuples of variables in the original model, allow the constraints of the problem to be represented more easily, propagating better.…”
Section: Review Analysismentioning
confidence: 99%